2014
DOI: 10.1016/j.neuron.2014.08.048
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency in LRP6-Mediated Wnt Signaling Contributes to Synaptic Abnormalities and Amyloid Pathology in Alzheimer’s Disease

Abstract: SUMMARY Alzheimer’s disease (AD) is an age-related neurological disorder characterized by synaptic loss and dementia. The low-density lipoprotein receptor-related protein 6 (LRP6) is an essential co-receptor for Wnt signaling and its genetic variants have been linked to AD risk. Here we report that neuronal LRP6-mediated Wnt signaling is critical for synaptic function and cognition. Conditional deletion of Lrp6 gene in mouse forebrain neurons leads to age-dependent deficits in synaptic integrity and memory. Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
199
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(206 citation statements)
references
References 71 publications
3
199
2
2
Order By: Relevance
“…Previously, broad-spectrum Wnt antagonists have been shown to affect synaptic structure, plasticity, and cognitive functions in adult organisms (37)(38)(39)(40)(41). However, there are 19 vertebrate Wnts, and which Wnt is essential for these functions in the adult brain in vivo remains unknown.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, broad-spectrum Wnt antagonists have been shown to affect synaptic structure, plasticity, and cognitive functions in adult organisms (37)(38)(39)(40)(41). However, there are 19 vertebrate Wnts, and which Wnt is essential for these functions in the adult brain in vivo remains unknown.…”
Section: Resultsmentioning
confidence: 99%
“…62 This study showed that neuronal LRP6 deficiency contributed to significant memory impairment, impaired long-term potentiation induction, correlating with learning and memory, and increased expression of glial fibrillary acidic protein and ionized calcium-binding adaptor molecule 1 (Iba1), markers for astrocyte and microglia activation, respectively. 62 Furthermore, the study reported that LRP6 deficiency significantly increased mouse endogenous Aβ40 and Aβ42 levels in the brain compared with control mice. 62 Despite evidence demonstrating the relevance between LRP6 and Aβ levels, the researchers designed in vitro experiments in human neuroblastoma SH-SY5Y cells overexpressing human APP (SHSY5Y-APP) to confirm the in vivo results.…”
Section: Lrp6 Genetic Polymorphisms and Admentioning
confidence: 88%
“…They found that LRP6 regulated APP trafficking and processing to Aβ 62 and also reported that LRP6 levels and Wnt signaling were down-regulated in AD brains in comparison with controls. 62 All these studies showed that LRP6 deficiency contributed to the development of AD.…”
Section: Lrp6 Genetic Polymorphisms and Admentioning
confidence: 96%
See 2 more Smart Citations